What Do We Know About a Translator’s Day? - Hébert-Malloch, Louise (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractLittle is known about a translator’s day. I therefore undertook to videotape a professional translator’s work for approximately 5 weeks. The tapes were then analyzed both at a macroscopic and a microscopic level. The first analysis produced information about general characteristics of his work whereas the second tried to uncover things such as strategies used in problem solving. This article is the summary of a Master’s Thesis defended in 1999 at Glendon College, York University.